Qualitative parameters and nutritional potential of arboreal cotton silage - Figueira, Luiz Henrique Torres; Teodoro, Ana Lúcia; Cardoso, Daniel Barros; Sarmento, William Gabriel Costa; Silva, Dulciene Karla de Andrade; Moura, Mácio Farias de; Magalhães, André Luiz Rodrigues; Melo, Airon Aparecido Silva de (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate the qualitative parameters and nutritional potential of silage of arboreal cotton (Gossypium hirsutum) shoots. The experiment was carried out in a 4×2 factorial arrangement, for two silage forms (in natura or pre-dried), with four treatments, as follows: without additives (WA); with inoculant (WI); with 2% ground corn (GC); and with 2% ground corn with inoculant (GC+I). The fermentative quality and nutritional parameters of the silages were evaluated. Fermentative quality was better in the WI and GC+I silages. The dry matter content was higher in the pre-dried silage, while the crude protein contents of in natura silage were higher in the WA and WI treatments. The lowest values of neutral detergent fiber and acid-digested lignin were observed in the WI treatment, for pre-dried silage. Total digestible nutrients and total volume of gas were higher in the pre-dried silage, in the WI and GC treatments, respectively. In vitro dry matter digestibility was lower in WA silage, in both forms. Silage of arboreal cotton associated with inoculant or with inoculant with ground corn shows a better fermentation profile and improves the energy and nutritional values, both in natura and pre-dried forms; however, in natura silage is less laborious for rural producers.